A review on the modelling of wave-structure interactions based on OpenFOAM - Huang, Luofeng; Li, Yuzhu Pearl; Benites-Munoz, Daniela; Windt Windt, Christian; Feichtner, Anna; Tavakoli, Sasan; Davidson, Josh; Paredes, Ruben; Quintuna, Tadea; Ransley, Edward; Colombo, Marco; Li, Minghao; et al. (OpenCFD Ltd on behalf of the OpenFOAM Governance, 2022)
The modelling of wave-structure interaction (WSI) has significant applications in understanding natural processes as well as securing the safety and efficiency of marine engineering. Based on the technique of Computational Fluid Dynamics (CFD) and the open-source simulation framework - OpenFOAM, this paper provides a state-of-the-art review of WSI modelling methods. The review categorises WSI scenarios and suggests their suitable computational approaches, concerning a rigid, deformable or porous structure in regular, irregular, non-breaking or breaking waves. Extensions of WSI modelling for wave-structure-seabed interactions and various wave energy converters are also introduced. As a result, the present review aims to help understand the CFD modelling of WSI and guide the use of OpenFOAM for target WSI problems.
Keywords: Wave-structure interaction; Computational Fluid Dynamics; OpenFOAM